A arte rupestre no Brasil: questões de transferência e representação da informação como caminho para interpretação - Netto, Carlos Xavier de Azevedo (2001)
The issue of rock art representation has been preoccupying the archeologists whom discuss this cultural manifestation long ago. This preoccupation is manifested on the registration techniques of the rock panels as well a the forms of communication the information obtained on studies of this phenomenon. The present study aims to discuss the ways of representation the Rock Art utilized by the Brazilian archeologists and if it is possible to establish interpretative relationships since the representations done. Therefore, this study was conceived based on the concepts of the classificatory units of Rock Art in Brazil, which has as principle the function of transference of the observed information between peers of the Brazilian Archeologist community. Filled with the theoretic and methodological subsides of Information Science, as long as this is a information problem, the semiotics fundaments and the representation theory were consulted to handle with the proposed object. It was possible to observe the categorization of this concepts (e.g. analytical, synthetic and interpretative), highlighting the synonymy problems and the polissemia which were identified and that the rock art interpretation is inherent to the ways which the information about this manifestation is represented, confirmed by the category identification of interpretative concepts